The utilization of ink cap mushroom (Coprinus cinereus) on palm oil mill effluent degradation - Yohanes Bernard Subowo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2017)
A research on the utilization of ink cap mushroom (Coprinus cinereus) on Palm Oil Mill Effluent (POME) degradation was conducted. Palm oil in-dustry is an agricultural industry which keeps on developing in Indonesia. Aside from producing palm oil, this industry also generates POME. POME has high level of BOD and COD value thus it is dangerous for the environment. Coprinus cinereus was examined to degrade POME because of its ability to produce ligninases enzymes. The aim of this research was to evaluate ligninases enzymes produced by C. cinereus after the addition of inducers and its ability in degrading POME. Coprinus cinereus was cultivated on Defined Medium (DM) then the mycelia was harvested Inducers used in this study were CuSO4, KNO3 and sucrose. The suspension of Coprinus cinereus mycelia was used to degrade POME. The result showed that Coprinus cinereus could produce Laccase, Mangan Peroxidase and Lignin Peroxidase on DM. The addition of 200 μM CuSO4 and 10 mM KNO3 on DM could increase laccase activity by 62.92 %. Coprinus cinereus has ability to degrade Poly R-478 and POME. The treatment of 200 μM CuSO4 on media could increase the degradation of Poly R-478 by 19.32% after 9 days of incubation. The addition of 15 g/L sucrose on POME could increase decolorization by 75.26 % and COD reduction by 91.26 % after 27 days of incubation. Ink Cap Mushroom (Coprinus cinereus) can be used for POME degradation. The addition of sucrose and heating treatment would accelerate COD reduction.